2017
DOI: 10.1016/j.fertnstert.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of calcium ionophore during artificial oocyte activation demonstrate an effect on pregnancy rate? A meta-analysis

Abstract: AOA with calcium ionophore treatment after intracytoplasmic sperm injection (ICSI) results in a statistically significant improvement in fertilization, cleavage, blastulation, and implantation rates, as well as overall pregnancy and live-birth rates. The conclusion of this systematic review, demonstrating a strong effect of calcium ionophore use, is reassuring and promising, particularly for couples for whom ICSI alone yields poor fertilization rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Ca 2+ ionophores like ionomycin, calcimycin are currently used to overcome unexplained fertilization failure in couples, who repeatedly fail ICSI cycles (Fawzy et al, 2018;Norozi-Hafshejani et al, 2018). Recently, a meta-analysis indicated that use of Ca 2+ ionophores significantly improved fertilization and implantation rates in ICSI (Murugesu et al, 2017). However, Ca 2+ ionophores induce a single Ca 2+ transient, unlike the endogenous specific physiological pattern of Ca 2+ oscillations observed during normal fertilization (Rinaudo et al, 1997).…”
Section: Clinical Applications Of Plcζ and Future Directionsmentioning
confidence: 99%
“…Ca 2+ ionophores like ionomycin, calcimycin are currently used to overcome unexplained fertilization failure in couples, who repeatedly fail ICSI cycles (Fawzy et al, 2018;Norozi-Hafshejani et al, 2018). Recently, a meta-analysis indicated that use of Ca 2+ ionophores significantly improved fertilization and implantation rates in ICSI (Murugesu et al, 2017). However, Ca 2+ ionophores induce a single Ca 2+ transient, unlike the endogenous specific physiological pattern of Ca 2+ oscillations observed during normal fertilization (Rinaudo et al, 1997).…”
Section: Clinical Applications Of Plcζ and Future Directionsmentioning
confidence: 99%
“…Calcium ionophore treatment results in a statistically significant improvement of fertilization, blastulation, and implantation rates, as well as of pregnancy and live-birth rates. This demonstrates a strong positive effect of calcium ionophore use [12].…”
Section: Artificial Activation Of Oocytesmentioning
confidence: 74%
“…It has been found that embryo implantation and live birth rates were very low in patients with AOA after ICSI (1,11,13,14) and many pregnancies were lost during the first trimester (1) although it was not known if this was resulting from poor sperm quality and/or poor oocyte activation. Aneuploidy is high in human embryos produced by IVF, even in young women (29), suggesting that low implantation rates and early pregnancy lose reported in the previous studies may be partially due to embryonic aneuploidies originated from oocytes (29) and/or sperm (5).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial oocyte activation (AOA) is a method of mimicking the physiological cell signaling mechanisms to activate oocytes, and calcium ionophore A23187 is the most widely used AOA method in humans (2)(3)(4)(8)(9)(10)(11)(12). Deliveries of healthy babies have been reported since AOA by calcium ionophore was adopted (2)(3)(4)(9)(10)(11)(12). A systematic review of published reports demonstrated acceptable outcomes of calcium ionophore use, particularly for couples in which ICSI alone yielded poor or no fertilization (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation